MEASUREMENT ANALYSIS OF MERCURY IN WATER, SOIL, FISH, AND HAIR AROUND ARTISANAL AND SMALL-SCALE GOLD MINING (ASGM) (Case Study: Indigenous Kasepuhan Cisitu, Cibeber Subdistrict, Lebak Regency, Banten Province) - Natalia Manik, Desy
Artisanal and Small-scale Gold Mining(ASGM) located in area of Indigenous Kasepuhan Cisitu, Cibeber Subdistrict, Lebak Regency, Banten has been existing for 5 years. These existence has potential to contaminate aquatic environment and human health due to the discharge from amalgamation process directly to environment. Therefore, purpose of this study are measuring and analyzing Hg concentration of water and soil from amalgamation process ; calculating the bioaccumulation in fish and fish consumption risk analysis, as well as analyzing mercury concentration in hair descriptively with the health risk assessment in ASGM Kasepuhan Cisitu.There are 9 water samples, 8 soil samples, 2 fish samples, and 48 hair samples. Extracted water, soil, and fish samples then examined using GF-AAS, besides, extracted hair samples being examined using CV-AAS. Results show that 9 water samples have Hg concentrations below standard set PP 82/2001. Four of eight samples of soil are well below the standards set Environment Canada and Health Canada that states 6,6 mg/kg Hg concentration in soil, with 146,79 mg/kg as the high values of mercury concentration. The BCF’s estimation of Oreochromis mossambicus and Oreochromis niloticus are in range 2,308 – 10,231 L/kg. Besides, estimated daily exposure to mercury fish consumption is 0,25 ?g/kg Body Weight/day with Acceptable Daily Intake (ADI) is 0,01 ?g/kg Body Weight/ day. It concludes that O. niloticus and O. mossambicus are not safe to consume. But mercury exposure is not only caused by fish consumption, but also caused by other food consumption, such as rice. Therefore, there will be possibility of greater exposure from other consumption. Descriptive and epidemiology’s analysis based on mercury concentration in hair figure that age and mining’s proffesion show positive relation with the enhancement of mercury concentration in hair. This results conclude that there is a risk health assessment in ASGM Kasepuhan Cisitu, especially for the indigenous people.